Velopharyngeal dysfunction: a systematic review of major instrumental and auditory-perceptual assessments - Paniagua, Lauren Medeiros; Signorini, Alana Verza; Costa, Sady Selaimen da; Collares, Marcus Vinicius Martins; Dornelles, Sílvia (International Archives of Otorhinolaryngology, 2013)
Introduction: Velopharyngeal dysfunction may cause impaired verbal communication skills in individuals with cleft lip and palate; thus, patients with this disorder need to undergo both instrumental and auditory-perceptual assessments.Objective: To investigate the main methods used to evaluate velopharyngeal function in individuals with cleft lip and palate and to determine whether there is an association between videonasoendoscopy results and auditory-perceptual assessments.Method: We conducted a systematic review of the literature on instrumental and auditory-perceptual assessments. We searched the PubMed, Medline, Lilacs, Cochrane, and SciELO databases from October to November 2012.Summary of findings: We found 1,300 studies about the topic of interest published between 1990 and 2012. Of these, 56 studies focused on velopharyngeal physiology; 29 studies presented data on velopharyngeal physiology using at least 1 instrumental assessment and/or 1 auditory-perceptual assessment, and 12 studies associated the results of both types of assessments. Only 3 studies described in detail the analysis of both methods of evaluating velopharyngeal function; however, associations between these findings were not analyzed.Conclusion: We found few studies clearly addressing the criteria chosen to investigate velopharyngeal dysfunction and associations between videonasoendoscopy results and auditory-perceptual assessments.
Keywords: Cleft Palate; Communication Disorders; Velopharyngeal Sphincter